Italy: a case of mutating populism?. Issue 2 (23rd February 2016) - Verbeek, Bertjan; Zaslove, Andrej
Abstract : Italy is often presented as a showcase of populist parties. In the 2013 parliamentary elections, half of the Italian electorate voted for a party that has been labelled populist. During the 1994–2011 period, Italy witnessed four coalition governments dominated by populists. In line with the framework guiding this special issue, Italy thus offers a unique opportunity to trace the reactions of political and societal actors to populists in government. We propose that it is necessary to examine not only how populism's opponents react, but also how fellow populists respond. Indeed, we observe in Italy, on the one hand, what we will call mutating populism and, on the other hand, a peculiar mixture of paralysis, antagonism, and imitation by their opponents. This contribution is structured as follows: first, we describe Italian populism in the context of the end of the Italian First Republic and the emergence of the new party system under the Second Republic. In the process we discuss events under the four Berlusconi governments (1994–1995; 2001–2005; 2005–2006; 2008–2011). In each phase, we distinguish between populist and anti-populist contenders. We also describe the reactions abroad to governing Italian populists, especially within the European Union.